Non-Profit Organozation Partnership In Toapekong Gotong Cultural Events - Kristianto, Johanes; Hendratmoko, Agustinus Welly (Acintya, 2025)
Partnership is an important aspect in managing organization, included nonprofit organization. Unlike profit organizations that struggled from their business activity resulting in a return, the nonprofit organization settled because its organization was supported by a partner. The method used in this study is a qualitative approach that focuses on the partnership model and impacts its partnership. Author interviewed five informants that qualified in those fields, in particular in art management and tourism. data were collected through semi-structured interviews, transcribed verbatim, and analyzed using thematic coding and data reduction. This study resulted in a partnership between Perkumpulan Boen Tek Bio with Culture and Tourism Department of Tangerang City existing on the fourth quadrant called Co-optation and Gradual Absorption. This partnership impacted three aspects, social, economy, and culture.